Challenges in Recognizing Indigenous Peoples' Rights in Mining Licensing in Indigenous Areas - Ari Purwadi (Journal of Adat Recht, 2025)
The mining sector is the backbone of the Indonesian economy, contributing significantly to national GDP. However, the expansion of the mining industry also has a direct impact on indigenous communities who have lived and managed their territories for generations but have not yet received formal legal recognition from the state. In practice, mining permits are often issued on customary lands without the participatory involvement of indigenous communities. This is despite the fact that indigenous communities have been recognized in the 1945 Constitution and Constitutional Court Decision No. 35/PUU-X/2012, and they have the normative right to be involved through the principle of Free, Prior, and Informed Consent (FPIC). This study aims to analyze the legal challenges and policy weaknesses in recognizing indigenous peoples' rights in mining permits in Indonesia. The method used is a normative legal approach with an analysis of legislation, case studies of conflicts in several customary territories, as well as a review of academic literature and reports from independent institutions. The results show that the absence of recognition of indigenous territories in national spatial planning, weak FPIC regulations, and overlapping policies between the mining and forestry sectors exacerbate the vulnerability of indigenous communities. This study recommends the legalization of FPIC, the establishment of a national customary recognition institution, and the harmonization of sectoral policies as steps towards ecological justice and sustainable constitutional protection.